PENGAWETAN TIGA JENIS KAYU UNTUK BARANG KERAJINAN MEMAKAI DUA JENIS BAHAN PENGAWET BOR SECARA RENDAMAN DINGIN - Sasa Abdurrohim (Jurnal Penelitian Hasil Hutan, 1992)
Three  Wood species,  i.e.  tusam  (Pinus  merkusii  Junh.  et De Vr.), karet  (Hevea brasiliensis Muell. Arg.) and jeungjing paraserianthes falcataria (L.)  Nielsen)   were  treated  with  two  bor preservatives  using cold soaking   method.  The  two preservatives  used  were  borax at  5  %  level  and  the  mixture  of  borax  and  boric acid  at  10  %  level.   The soaking periods  were  1,  3,  5 and 7 days. Forty  samples  of  the  size 5  x 5  x 50  cm  were  used for  each species  and  each treatment  in  thisn experiment.   The avemge moisture  content of the samples for each species  were 29 .9 %, 31. 9%  and 30.3% respectively.The results  showed   that  two species,  i.e. tusam  and karet  achieved  the  minimum standard on preservative  retention and pentatiue.   The  required  minimum retention for  borex  preservative  is 8. 7 kg/m3, whereas  for  the mixture of borax  and boric acid is 8.4 kg/m3.  The required  minimum penetration for both preservatives is 10 mm.The .study  recommended   that  tusam  should be treated in 5 days  using borax preservative  or  1  day  using the  mixture of   borax  and  boric,  both  with  cold  soaking  method.  The  treatment for  karet  was  recommended   to use the  mixture of borax  and  boric  acid  within 3 days.